Molecular Mechanisms of the Interactions of N-(2-Hydroxypropyl)methacrylamide Copolymers Designed for Cancer Therapy with Blood Plasma Proteins - Larisa Janisova; Andrey Gruzinov; Olga V. Zaborova; Nadiia Velychkivska; Ondřej Vaněk; Petr Chytil; Tomáš Etrych; Olga Janoušková; Xiaohan Zhang; Clement Blanchet; Christine M. Papadakis; Dmitri I. Svergun; et al. (MDPI AG, 2020)
The binding of plasma proteins to a drug carrier alters the circulation of nanoparticles (NPs) in the bloodstream, and, as a consequence, the anticancer efficiency of the entire nanoparticle drug delivery system. We investigate the possible interaction and the interaction mechanism of a polymeric drug delivery system based on N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers (pHPMA) with the most abundant proteins in human blood plasma—namely, human serum albumin (HSA), immunoglobulin G (IgG), fibrinogen (Fbg), and apolipoprotein (Apo) E4 and A1—using a combination of small-angle X-ray scattering (SAXS), analytical ultracentrifugation (AUC), and nuclear magnetic resonance (NMR). Through rigorous investigation, we present evidence of weak interactions between proteins and polymeric nanomedicine. Such interactions do not result in the formation of the protein corona and do not affect the efficiency of the drug delivery.